Exploring the Relationship Between Service Marketing, Brand Trust, and Brand Value in Cross-Border E-Commerce: The Moderating Effect of Product Market Strategy - Li, Qiangyan (Journal of Global Economy, Business and Finance, 2026)
Brand value plays a central role in determining the international competitiveness of enterprises. However, existing research has yet to fully elucidate the mechanisms through which service marketing influences brand value via brand trust, nor has it sufficiently addressed the contingent role of product market strategy in this relationship. To address this gap, this study draws on service marketing theory and brand management theory to investigate the impact of service marketing on brand value in cross-border e-commerce, examining both the mediating role of brand trust and the moderating role of product market strategy. Based on an analysis of 212 survey responses, the empirical results indicate that service marketing significantly enhances brand value in cross-border e-commerce. Moreover, brand trust partially mediates the relationship between service marketing and brand value. In addition, product market strategy positively moderates the effect of service marketing on brand value, suggesting that the strength of this relationship depends on the strategic orientation of the firm. These findings imply that cross-border e-commerce enterprises can effectively strengthen their brand competitiveness in international markets by optimizing service marketing strategies, fostering brand trust, and aligning product market strategies with brand development objectives.